“Space” in the Novel, Futon by Tayama Katai - Tammawiwat, Sunisa; Panitwiboon , Chalantorn (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
Futon is a novel written by Tayama Katai and the story was based on his real-life experience involving his female student named Okada Michiyo. Futon is a naturalism novel that strongly expresses humans’ dark side, especially desires, sexual longings, and jealousy. Moreover, the story is also full of situations that highlight morality challenges. This article aims to study the spatial meaning of different places in the story including, the house, the capital city, the hometown, and the bedroom. It was found that the “spaces” portrayed in the novel were not just physical spaces. The male protagonist's house represented a space of change. The capital city also represented the meaning of space as Yoshiko’s pursuit of freedom. In the story, the spaces also reflected the ideas of Japanese people during the Meiji era that they were trying to change and seek their own freedom by heading towards the capital city to pursue their dreams, new life, and gender equality. However, society at that time did not fully accept women's equal rights to men. The hometown was, therefore, a space of acceptance and submission of women to be under patriarchy. As for the bedroom, it was not only represented as a symbol of a carnal desire but also a space of memory and nostalgia that could never be regained.